Improving estimates of species distribution change by incorporating local trends. Issue 3 (2nd December 2020) - Barnett, Lewis A. K.; Ward, Eric J.; Anderson, Sean C.
Abstract : A common goal in ecology and its applications is to better understand how species' distributions change over space and time, yet many conventional summary metrics (e.g. center of gravity) of distribution shifts may offer limited inference because such changes may not be spatially homogenous. We develop a modeling approach to estimate a spatially explicit temporal trend (i.e. local trend), alongside spatial (temporally constant) and spatiotemporal (time‐varying) components, to compare inferred spatial shifts to those indicated by conventional metrics. This method is generalizable to many data types including presence–absence data, count data and continuous data types such as density. To demonstrate the utility of this new approach, we focus on the application of this model to a community of well‐studied marine fish species on the US west coast (19 species, representing a wide range of presence–absence and densities). Results from conventional model selection indicate that the use of the model accounting for local trends is clearly justified for over 89% of these species. In addition to making more parsimonious and accurate predictions, we illustrate how estimated spatial fields from the local trend model can be used to classify regions within the species range where change is relatively homogenous. Conventional summary metrics, such as center of gravity, can then be calculated on each such region or within previously defined biogeographic boundaries. We use this approach to illustrate that change is more nuanced than what is expressed via global metrics. Using arrowtooth flounder Atheresthes stomias as an example, the observed southward shift over time in the center of gravity is not reflective of a uniform shift in densities but local trends of decreasing density in the northern region and rapidly increasing density at the southern edge of the species' range. Thus, estimating local trends with spatiotemporal models improves interpretation of species distribution change.